A timely systematic review on pangolin research, commercialization, and popularization to identify knowledge gaps and produce conservation guidelines. (April 2021) - Heighton, Sean P.; Gaubert, Philippe
Abstract: Conservationists can benefit from encompassing research, social, and economic aspects of conservation issues to produce holistic conservation guidelines. Pangolins have become a taxon of conservation eminence as they continue to be poached and trafficked to extinction, and have been mislabeled as potential intermediary hosts of SARS-CoV-2 which is responsible for the COVID-19 pandemic. Applying a systematic review approach, we extracted pangolin-related publications since 1865 from five research databases (814 publications), as well as data on 5296 patents, online news trends (43, 176 articles) and societal interest (Google Trends and Wikipedia Pageviews). Although we detected a significant increase in pangolin-related publications through time, we observed glaring knowledge gaps in contextually important categories including immunology, education, and implications of trade or poaching to populations. All eight species have literature knowledge gaps, however African species are less represented. Fifteen African range-states have no pangolin literature, while the number of publications with non-range-state lead authors increased from 8% to 42.9% since 2017. Pangolin media output and societal interest have remained low relative to other flagship species, however COVID-19 is shifting these dynamics. Pangolin patent production was linked to Traditional Chinese Medicine, which was neither driven by science nor traditional pharmacopoeia. To help conserve pangolins, we suggest increased effort in health and field-based conservation research, while directing more attention towards Africa. We highlight the importance of maintaining range-author contributions, and of factors that may lead to increased public interest in pangolins. Our approach can be used to devise integrative conservation guidelines for other species. Highlights: The first systematic, multidisciplinary review on pangolins Pangolin research trends are rising faster than modern science research trends Major knowledge gaps are prevalent by research category, species and range-state COVID-19 has increased public interest in pangolins to new record levels Patent production is seemingly not driven by either science or pharmacopoeia